CAPt’n of Actin Dynamics: Recent Advances in the Molecular, Developmental and Physiological Functions of Cyclase-Associated Protein (CAP) - Rust, Marco B.; Khudayberdiev, Sharof; Pelucchi, Silvia; Marcello, Elena (Frontiers in Cell and Developmental Biology, 2020)
Cyclase-associated protein (CAP) has been discovered three decades ago in budding yeast as a protein that associates with the cyclic adenosine monophosphate (cAMP)-producing adenylyl cyclase and that suppresses a hyperactive RAS2 variant. Since that time, CAP has been identified in all eukaryotic species examined and it became evident that the activity in RAS-cAMP signaling is restricted to a limited number of species. Instead, its actin binding activity is conserved among eukaryotes and actin cytoskeleton regulation emerged as its primary function. However, for many years, the molecular functions as well as the developmental and physiological relevance of CAP remained unknown. In the present article, we will compile important recent progress on its molecular functions that identified CAP as a novel key regulator of actin dynamics, i.e. the spatiotemporally controlled assembly and disassembly of actin filaments (F-actin). These studies unraveled a cooperation with ADF/Cofilin and Twinfilin in F-actin disassembly, a nucleotide exchange activity on globular actin monomers (G-actin) that is required for F-actin assembly and an inhibitory function towards the F-actin assembly factor INF2. Moreover, by focusing on selected model organisms, we will review current literature on its developmental and physiological functions, and we will present studies implicating CAP in human pathologies. Together, this review article summarizes and discusses recent achievements in understanding the molecular, developmental and physiological functions of CAP, which led this protein emerge as a novel CAPt’n of actin dynamics.